Comparison of Cutting Performance of Artificial and Natural Diamond Tools in Ultra-precision Machining of Electroless Nickel Plated Die Materials - Pramanik, Alokesh; Soon, Neo; Rahman, Mustafizure; Li, X; Sawa, M; Maeda, Y (Singapore Institute of Manufacturing Technology, 2004)
This paper deals with the performance of natural and artificial diamond cutting tools in ultra-precision machining of electroless nickel for a cutting distance of 200km. Comparison of cutting performance is in terms of flank wear, crater wear, surface roughness, surface appearance and cutting forces. The experimental results show that in terms of surface roughness, both natural and artificial diamond cutters performed just as well. Both cutter types also exhibited similar crater and flank wear pattern but the amount of wear is different. The natural diamond cutter has minimal crater and flank wear compare to artificial diamond cutter. During machining, cutting forces are significantly lower in for natural diamond cutter compared to the artificial one.